The effects of MTG catalysis on methanol mobility in ZSM-5. Issue 13 (12th June 2018) - Matam, S. K.; O'Malley, A. J.; Catlow, C. R. A.; Suwardiyanto,; Collier, P.; Hawkins, A. P.; Zachariou, A.; Lennon, D.; Silverwood, I.; Parker, S. F.; Howe, R. F.
Abstract : QENS shows that methanol is immobile in a fresh ZSM-5 catalyst and one used for methanol conversion at 623 K, but undergoes isotropic rotation within the mesopores generated in a catalyst used for methanol conversion at 673 K. Abstract : We analyse the dynamics of methanol in ZSM-5 catalysts both with and without the hydrocarbon pool, resulting from the methanol to gasoline (MTG) reaction taking place at 623 K and 673 K for three days, to determine the effects of catalyst use on molecular mobility. Using quasielastic neutron scattering (QENS), we observe that methanol is immobile on the QENS instrumental time scale in the fresh catalyst (ZSM-5-F) and in the sample used to convert methanol for 3 days at 623 K (ZSM-5-623). However, in zeolite ZSM-5-673 (MTG at 673 K for 3 days) we observe isotropic methanol rotation with an immobile fraction of 0.58 and a rotational diffusion coefficient of D R = 3 × 10 10 s −1 . The observed differences between the zeolites in methanol dynamics are attributed to the development of mesoporosity in ZSM-5-673 due to the high reaction temperature of 673 K, leading to dislodgement of lattice Al as is evident from NMR data.